Culture et pratiques numériques juvéniles : Quels usages pour quelles compétences ? - Florian Dauphin (Université de Provence, 2012)
This article deals with teenagers' digital culture and practices. Quantitative and qualitative research has shown that Information and Communication Technologies (ICT) become more and more present in young people's everyday life. The latter are commonly considered as technology experts by their elders. We will put into perspective the existing studies on the subject. Researches generally show that teenagers have a special relationship with ICT based on communication, social networking, recreational activities, consumption, and also show that the skills they apply seem hardly reconcilable with the reasonable use prescribed by the educational institutions.